Strategy of Apology in Buginese: A Sociolinguistic Study - Zulkhaeriyah; Noer Jihad Saleh; Abdul Hakim Yassi; Fathu Rahman (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
The research aims to elaborate the apology strategies employed by Buginese speaker and explore the structure of apology based on social relation between interlocutors. The result reveals that Buginese speaker use various strategy of apology in apologizing but the most dominant apology strategy do Buginese speakers employ in apologizing is acknowledgment responsibility with four substrategies expressing lack of intent, expressing self deficiency, accepting blame, expressing of embarrassment. Moreover, the complaint, showing the effort, showing desire, and brushing off the incident as unimportant is exist in the data as modification of apology strategy from six scholars and others prior researcher. Therefore, it can conclude that Buginese people employ indirect apology such as acknowledgment of responsibility, explanation, an offer of repair, interjection, address term in their apology eventhough it combines with direct apology whether in the beginning, middle or in the end of utterances or response to show her/his polite behavior to others.